Porous squeeze film bearing with rough surfaces lubricated by a Bingham fluid - Walicka, Anna; Walicki, Edward; Jurczak, Paweł; Falicki, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
In the paper the effect of both bearing surfaces and the porosity of one bearing surface on the pressure distribution and load-carrying capacity of a squeeze film bearing is discussed. The equations of motion of a Bingham fluid in a bearing clearance and in a porous layer are presented. Using the Morgan-Cameron approximation and Christensen theory of rough lubrication the modified Reynolds equation is obtained. The analytical solutions of this equation for a squeeze film bearing are presented. As a result one obtains the formulae expressing pressure distribution and load-carrying capacity. A thrust radial bearing is considered as a numerical example.
Keywords: viscoplastic fluid; Bingham model; thrust bearing; porous layer; Christensen roughness